“THIS ISN'T A PICASSO, IT'S A FERRARI”: PRESENTISM, PRECARITY AND DEPENDENCE IN NEW MEDIA ART PRACTICES - Vasudevan, Roopa (AoIR Selected Papers of Internet Research, 2021)
New media artists—and, more broadly, those who consider themselves to be “creative” technologists—increasingly find themselves questioning whether or not to use tools that are owned or administered by companies that engage in activity that they consider to be problematic, such as surveillance, cooperation with discriminatory law enforcement practices, or toxic work cultures. However, it is difficult to conceive of a tech-based art practice that functions without utilizing $2 of the dominant technologies that we find ourselves surrounded by on a regular basis. As a result, artists who work with technology are inevitably thrust into perpetually shifting situations or environments, controlled by the tech industry, which then directly impact the creation of their work; its longevity; and, often, their own perceptions of it. This paper represents the beginnings of an investigation into the relationships between new media artists, the tools they use for their work (including data sources and APIs, hardware and software, operating systems, and project storage), and those who control these technologies. I seek to portray this creative community as one that exists in a state of constant uncertainty, and that finds itself in this position at the behest of the interests of the tech industry—which both uses artists’ work as a way of positioning itself as cutting-edge and original, and as a means of locating potential sites of intentional misuse and subversion. Artists are thus forced to constantly adapt their processes to the demands of those who control the technology, ultimately reinforcing the authority of these dominant systems.